Kesadaran Hukum Masyarakat Pedesaan Untuk Bercerai di Pengadilan (Studi Kasus di Desa Bantarbolang, Kabupaten Pemalang) - Iwan Zaenul Fuad; Miftah Husaeni (Jurnal Hukum Islam, 2020)
This research explores the legal awareness and implications of divorce in court on communities in Bantarbolang Village, Pemalang, Central Java Province, Indonesia. This legal sociology research uses a qualitative approach. The primary data source is the divorcee outside the court. Secondary data sources are primary and secondary legal materials. The analysis technique uses an interactive model. The results showed, the legal awareness of the Bantarbolang community about divorce in court was not evenly distributed, where 21 couples were divorcing in court and 5 outside the court. They know that a divorce must be in court, but it is not carried out. The implications of legal awareness about divorce outside the court are: 1) administratively, they are still bound as husband and wife, because they do not have a divorce certificate so that if they marry someone else, they are done in a series; 2) psychological implications for children and if the couple remarries Siri, then the child born becomes the child born outside the marriage; 3) implications of the split between the extended family of the couple; 4) implications for the social order, due to the uncertainty of the status of husband and wife and the nasab of children from a Siri marriage. Therefore, prevention should be carried out through outreach to the public about the legal consequences of divorce outside the court.